The Development Model of public Junior High School Teacher Performance in Semarang City - Wati, Alfi Setyo; Yanto, Heri; Kardoyo, Kardoyo (Educational Management, 2022)
A teacher's performance is determined by the quality and quantity of the work they complete while carrying out their responsibilities, which include creating lesson plans, implementing instruction, collecting data from assessments, and analyzing assessments. Many factors influence teacher performance, including principal leadership, organizational culture, MGMP participation, and job satisfaction. This research aims to determine the direct and indirect influence of school principal leadership, organizational culture, and MGMP participation on teacher performance through job satisfaction of Junior High School teachers in Semarang City.The sampling technique used in this research was proportional random sampling with 200 total sample teachers taken from eight state schools in Semarang City. This data analysis uses path analysis using Amos 23.0 program. Questionnaires were used as data collection instruments.The research results show that the principal's leadership has a direct influence on organizational culture and MGMP participation; organizational culture has a direct effect on MGMP participation; the principal's leadership has a direct effect on job satisfaction and organizational culture has a direct effect on job satisfaction; MGMP participation does not affect job satisfaction; Job satisfaction has a direct effect on teacher performance and MGMP participation has a direct effect on teacher performance. Meanwhile, for indirect effects, job satisfaction can mediate the influence of the principal's leadership on teacher performance; Job satisfaction can mediate organizational culture on teacher performance, while job satisfaction is not able to mediate the effect of MGMP participation on teacher performance.